Definition of mass and production of equations of general relativity - Krikos, Constantinos (Open Science Journal, 2020)
From the measurements of the anisotropies of the cosmic background radiation at the present time, we get a value for the density parameter (Ω(t)) near to unit, i.e. Ω(t) ∼ 1. The value of the density parameter determines if the Universe is open (Ω(t) < 1), flat (Ω(t) = 1) or closed (Ω(t) > 1)). This result forces us to assume that the boundary of the Universe is a 2D flat space, i.e. the R2 , since its interior is a 3D space as we conceive it. The R2 space is characterized by isotropy and homogeneity. It is a simply connected space and that it does not exhibit any particular characteristic anywhere. These attributes are expressed by a circle of an infinite radius in the center of which is an observer, at every point in the Universe. Since circle is the geometric object from which all other conic sections produced, then we shall examine the equations that characterize them and the consequences of their mappings in the interior of the Universe through one to one correspondences.